DMF-T index in patients undergoing radiation therapy with LINAC X-ray radiation for head and neck cancer at Department of Radiotherapy, Dr. Hasan Sadikin Hospital - Sabrina, S.; Azhari, A.; Aripin, Dudi (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2007)
Radiation therapy for head and neck cancer frequently caused severe salivary gland dysfunction. The salivary gland dysfunction possibly decreased the protective function of saliva and caused dental caries. The purpose of this study was to obtain an illustration about DMF-T index in patient undergoing radiation therapy with LINAC X-ray radiation for head and neck cancer at Department of Radiotherapy, Dr. Hasan Sadikin Hospital in January-February 2007. The study was a simple descriptive. The study was conducted on 7 males and 9 females undergoing radiation therapy with LINAC X-ray radiation for head and neck cancer. The ages of patient are between 37 years and 77 years. The severity of caries was measured by DMF-T index. DMF-T index in 16 patient undergoing radiation therapy with LINAC X-ray radiation for head and neck cancer at Dr. Hasan Sadikin Hospital is 10.6 as the result of this study. The conclusion of this study showed that the DMF-T index in 16 patient undergoing radiation therapy with LINAC X-ray radiation for head and neck cancer at Dr. Hasan Sadikin Hospital had very high grade based on WHO classification, which the value was over 6.6.